A Novel Type of Splicing Enhancer Regulating Adenovirus Pre-mRNA Splicing - Mühlemann, Oliver (American Society for Microbiology, 2000)
Splicing of the adenovirus IIIa pre-mRNA is subjected to a temporal regulation, such that efficient IIIa 3′ splice site usage is confined to the late phase of the infectious cycle. Here we show that IIIa pre-mRNA splicing is activated more than 200-fold in nuclear extracts prepared from late adenovirus-infected cells (Ad-NE) compared to uninfected HeLa cell nuclear extracts (HeLa-NE). In contrast, splicing of the β-globin pre-mRNA is repressed in Ad-NE. We constructed hybrid pre-mRNAs between IIIa and β-globin in order to identify the minimal IIIa sequence element conferring enhanced splicing in Ad-NE. Using this approach, we show that the IIIa branch site/pyrimidine tract functions as a Janus element: it blocks splicing in HeLa-NE and functions as a splicing enhancer in Ad-NE. Therefore, we named this sequence the IIIa virus infection-dependent splicing enhancer (3VDE). This element is essential for regulated IIIa pre-mRNA splicing in Ad-NE and sufficient to confer an enhanced splicing phenotype to the β-globin pre-mRNA in Ad-NE. We further show that the increase in IIIa splicing observed in Ad-NE is not accompanied by a similar increase in U2AF binding to the IIIa pyrimidine tract. This finding suggests that splicing activation by the 3VDE may operate without efficient U2AF interaction with the pre-mRNA. Importantly, this report represents the first description of a splicing enhancer that has evolved to function selectively in the context of a virus infection, a finding that adds a new level at which viruses may subvert the host cell RNA biosynthetic machinery to facilitate their own replication.